Stranded with her forbidden knight - Oliver, Melissa (Oliver, Melissa (Romance author). Protectors of the crown., 2024)
"Lady Elowen is traveling to her loveless arranged betrothal when she’s rescued from a storm by Lord Simon Trebarr—the enigmatic knight whose family has long been enemies of her own. She should hate him, yet an unwanted attraction has always simmered whenever he’s near… Within the walls of Simon’s Cornish castle, can Elowen resist experiencing passion before condemning herself to a life without it…even if it’s with the man who should be her enemy?" --